x+x-(1/2x)=6

Simple and best practice solution for x+x-(1/2x)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+x-(1/2x)=6 equation:



x+x-(1/2x)=6
We move all terms to the left:
x+x-(1/2x)-(6)=0
Domain of the equation: 2x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
x+x-(+1/2x)-6=0
We add all the numbers together, and all the variables
2x-(+1/2x)-6=0
We get rid of parentheses
2x-1/2x-6=0
We multiply all the terms by the denominator
2x*2x-6*2x-1=0
Wy multiply elements
4x^2-12x-1=0
a = 4; b = -12; c = -1;
Δ = b2-4ac
Δ = -122-4·4·(-1)
Δ = 160
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{160}=\sqrt{16*10}=\sqrt{16}*\sqrt{10}=4\sqrt{10}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-4\sqrt{10}}{2*4}=\frac{12-4\sqrt{10}}{8} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+4\sqrt{10}}{2*4}=\frac{12+4\sqrt{10}}{8} $

See similar equations:

| 2x-11=-31 | | (3y-2)/(2-5y)=1/2 | | -19.17+16s=4.5s+0.43+17.1s | | A=-6w | | (2x-7)-(x-4)=2 | | 3(7-9)=x | | 3(d+13)-14=85 | | 2x2-2=0 | | (2x-13)^2=8 | | (1/125)2x-2*625x=125 | | -6+(2x+11)=37 | | 7/3+3m/5=56/15 | | -4(x-3)=-x. | | -4.2-15.8d=-4.08-15.7d | | -85-7x=75-15x | | 37-b=32 | | (7-2x)-(4-x)=2 | | 6-3c=15 | | 7p-()3p+4=-2(2p-1)+10 | | 3.1(x+2)-1.5x=5.2(x+4) | | 6-x-4=5x+2x-14 | | (2x-6)^2=39 | | 1/10y=14 | | (X+11)(x+11)=104 | | 2(g+2)=5g-4 | | b/11-5b/11=36/11 | | 3x-69;x=3 | | -14-y=16+4y | | -1/2x+3=2 | | (x-4)-(2x-7)=2 | | 5(d+37)-(-12)=27 | | 1/24y=2 |

Equations solver categories